Efecto del impacto de actividades antrópicas en arroyos pampeanos sobre las comunidades acuáticas de hifomicetes - Kravetz, Sebastián (2020)
Aquatic hyphomycetes are among the most important microorganisms in the decomposition processes of plant material in freshwater courses. In Pampean region, rivers and streams have suffered modifications, which have contributed to their deterioration, as a result of anthropogenic activities. This study was carried out between 2014 and 2019 in 36 stretches of 21 streams, situated in the NE of the Pampas region. Experiments of leaf litter decomposition and colonization of hyphomycetes were carried out in some selected streams with impacted sites as well as on non-impacted ones. Moreover, alkaline phosphatase, β-glucosidase and cellobiohydrolase enzymatic activities were analyzed. A total of 89 species of aquatic hyphomycetes were recorded and 50 are the first report to Argentina. Conidia in plankton were found in all streams. Furthermore, the highest number of species occurred in streams with arboreal riparian vegetation. On the other hand, sites affected by livestock farming and urban-industrial impacts had the lowest values. The associations between presence and richness of species with environmental variables showed correlations with the concentrations of nutrients, dissolved oxygen and humic acids. The decomposition was variable according to the type of leaf litter and stream. The maximum rates were registered in sites with invasion of honey locust, which also had the highest sporulation rates. It was followed by urban environments with highly variable results according to leaf litter type, while the lowest amounts were found in streams impacted by livestock farming. The presence of hyphomycetes decomposers of leaf litter were corroborated in all colonization experiments. The non-impacted sites and the ones with honey locust invasion had a higher number of species than those impacted by livestock farming and urbanizations. When comparing functional aspects such as decomposition, these variations were only evident in a few cases. The enzymatic activities did not show significant differences. The fungicide treatments decreased the activities and standard deviations so the functional heterogeneity of decomposers community is strongly associated with fungi. It is concluded that a high variety of aquatic hyphomycetes inhabits the streams of the Pampas region. There is a response of the hyphomycetes to impacts, which is significantly manifested at structural, but not at functional level. The livestock farming and urban-industrial activities decrease time colonization and species richness in plankton and leaf litter, while the honey locust invasion increases them. Leaf litter decomposition is affected only when the impact is strong. Aquatic fungi contribute in a significant proportion to the extracellular enzymatic activities, but enzymes are not affected by impacts.